A half-century record of coral skeletal P/Ca reveals late 20th century nutrient pollution in Port Dickson, Malaysia. (August 2022) - Chen, Mengli; Chia, Hao Kai; Martin, Patrick; Lee, Jen Nie; Bettens, Ryan P.A.; Tanzil, Jani T.I.
Abstract: Anthropogenic nutrient pollution has been identified as one of the key stressors of coastal ecosystems. However, the paucity of long-term nutrient records limits our understanding of both the extent of nutrient pollution as well as of the ecological impacts. Here, using coral skeletal phosphorus (P/Ca), we reconstructed a half-a-century record of seawater phosphate at Port Dickson, Malaysia. The P/Ca in the coral revealed an up to 8-fold increase in coral P/Ca from the late 1970s to 2000s, likely linked to increases in fertilizer use (R 2  = 0.47) and variabilities in rainfall (R 2  = 0.17). The rise in coral P/Ca in coincided with a contemporaneous 18 % decrease in coral skeletal density, suggesting phosphate enrichment may impact the growth and structural integrity of reef-building corals. Given the importance of both agriculture and heavy reliance on coral reefs by populations in Southeast Asia, our study highlights continue the need to develop environmental management upstream of coastal zones. Graphical abstract: Unlabelled Image Highlights: A half-century record of coral P/Ca is reconstructed from Port Dickson, Malaysia. Pre-pollution seawater phosphate baseline of ~0.1 μM as estimated from coral P/Ca. The coral P/Ca increased up to 8-fold over the late 20th century. The increase in P/Ca likely caused by land-based human activities and rainfall. The rise in coral P/Ca coincided with 18 % decrease in coral skeletal density.